Підзвітність в органах виконавчої влади: особливості суб'єктного складу - Синкова, О.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Subject composition of administrative legal relations of accountability, their classification, which based on the type of legal relationships of accountability is is explored. The necessity of subsequent regulation of legal relationships of accountability in legal acts, which regulate legal status of organs of executive power, is grounded.